A qualitative exploration of attitudes towards the use of outcome measures in child and adolescent mental health services. (April 2017) - Sharples, Evelyn; Qin, Chuan; Goveas, Vinita; Gondek, Dawid; Deighton, Jessica; Wolpert, Miranda; Edbrooke-Childs, Julian
The aim of the present research was to explore clinician attitudes to outcome measures and, in particular, the facilitators and barriers to implementing outcome measures. An up-to-date exploration of clinician attitudes is especially needed in the context of recent policies on the implementation of outcome measures in child and adolescent mental health services (CAMHS), and because evidence suggests that there is a disparity between policy recommendations and the use of outcome measures in clinical practice. Semi-structured interviews were conducted with nine CAMHS clinicians from a Mental Health Trust in South London. Two levels of implementation emerged from the analysis: (1) the service level, regarding the implementation of outcome measures across a service to inform service improvement and (2) the session level, regarding the implementation of outcome measures within individual clinical sessions. The present research described training and ongoing support as a crucial facilitator of use at both service and session levels. This included help overcoming local contextual barriers, such as resources, information systems and administrative processes. The research showed that a balance is needed between a mandatory and uniform approach across a service and providing clinicians with support to use outcome measures with all service users for whom they are appropriate.